Increasing Awareness and Knowledge of Hoax News in Sakatiga Village: A Response to Globalization's Information Challenges - Bashir, Abdul; Sukanto, Sukanto; Hamira, Hamira; Hamidi, Ichsan; Dwi, Rosada Sintya (Sricommerce: Journal of Sriwijaya Community Services, 2023)
In the current era of globalization, information dissemination occurs rapidly through various mass media intermediaries. This presents new challenges, particularly for individuals residing in rural areas who may lack the necessary understanding to harness today's technological advances. One pressing issue is the widespread circulation of hoax news, primarily through social media platforms. This service initiative aims to enhance awareness and knowledge regarding hoax news in Sakatiga Village, Indralaya District, Ogan Ilir Regency. The implementation strategy revolves around a comprehensive socialization approach designed to raise public awareness, enhance comprehension, and empower residents with the skills to differentiate between hoax and genuine news. Additionally, it provides insights into relevant laws and outlines the necessary steps to take in the event of encountering hoax news